Racial and Ethnic Disparities in Survival of Children with ESRD - Ku, Elaine (J Am Soc Nephrol, 2017)
Observational studies have reported that black and Hispanic adults receiving maintenance dialysis survive longer than non–Hispanic white counterparts. Whether there are racial disparities in survival of children with ESRD is not clear. We compared mortality risk among non–Hispanic black, Hispanic, and non–Hispanic white children who started RRT between 1995 and 2011 and were followed through 2012. We examined all-cause mortality using adjusted Cox models. Of 12,123 children included for analysis, 1600 died during the median follow-up of 7.1 years. Approximately 25% of children were non-Hispanic black, and 26% of children were of Hispanic ethnicity. Non–Hispanic black children had a 36% higher risk of death (95% confidence interval [95% CI], 1.21 to 1.52) and Hispanic children had a 34% lower risk of death (95% CI, 0.57 to 0.77) than non–Hispanic white children. Adjustment for transplant as a time-dependent covariate abolished the higher risk of death in non–Hispanic black children (hazard ratio, 0.99; 95% CI, 0.88 to 1.12) but did not attenuate the finding of a lower risk of death in Hispanic children (hazard ratio, 0.59; 95% CI, 0.51 to 0.68). In conclusion, Hispanic children had lower mortality than non–Hispanic white children. Non–Hispanic black children had higher mortality than non–Hispanic white children, which was related to differences in access to transplantation by race. Parity in access to transplantation in children and improvements in strategies to prolong graft survival could substantially reduce disparities in mortality risk of non–Hispanic black children treated with RRT.